Disjunctures within conventional knowledge of black male homosexual identity in contemporary South Africa - Li, Xinling (Rhodes University, Faculty of Humanities, Department of Sociology, 2010)
This thesis provides a sociological understanding of how conventional knowledge of sexuality negates the identity formation of black gay men in contemporary South Africa. It investigates the coming out experiences of six black gay men in order to reveal the disjunctures between being black and being gay. The theoretical formation of disjuncture is pursued through examining a number of sociological, historical, psychoanalytical, and feminist approaches to identity, sexuality, and society; featuring specifically the theories of George Herbert Mead, Michel Foucault, and Judith Butler. The chosen research paradigm is symbolic interactionism, postulating both pragmatist"Ÿ and empiricist"Ÿ trends that lead to both interactionist and structuralist forms of argumentation. The interactionist approach to sexuality is central to the deconstruction of sexual conventions. It involves conceptualising modern sexuality in the landscapes of African colonial history and the global gay and lesbian movement. The prescribed literature on homosexuality is thus reviewed in conjunction with the South African gay and lesbian struggle, so as to spawn themes and perspectives for conducting life story interviews. The use of the life story interview favours the participants"Ÿ own view of the studied phenomenon, yet aims to depict the structural influence on homosexual identification. Following the qualitative research tradition, the data analysis is based on the interpretation of narratives. It illustrates interpersonal relationships and microscopic experiences that lead to the self-acceptance and self-actualisation of homosexuality. Within these processes, various disjunctures that exist between the cultural sanction of lifestyle and individual choice, between parents and children, between religious belief and personal desires, and between gender identity and sexual orientation are disclosed. The findings are associated with the historical transformation of masculinity in South Africa, sex role performance, and the heterosexualisation of desire. The solution to the proposed research problem is discussed through concepts of socialisation and gender conformity.
Keywords: Mead, George Herbert 1863-1931; Foucault, Michel, 1926-1984; Butler, Judith, 1956-; Gay men, Black -- South Africa; Lesbians -- South Africa; Gender identity -- South Africa; Homosexuality -- South Africa; Identity (Psychology) -- South Africa; Gender identity -- Social aspects